UMP contributes expertise in the development of halal products in Japan - Nur Laila, Afandi (2018)
Japan, 31 January- A Halal Audit monitoring visit was held in the Land Of The Rising Sun at two food processing facilities. Dr. Farhan Mohd Said, from Faculty of Chemical and Natural Resources Engineering (FKKSA) Universiti Malaysia Pahang (UMP) participated in the visit together with the auditors from Muslim Professional Japan Association (MPJA).